2013
DOI: 10.7863/jum.2013.32.2.303
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sonographically Guided Core Needle Biopsy and Excision in Breast Papillomas

Abstract: Objectives The aim of this study was to evaluate the clinical factors and sonographic features of benign papillomas of the breast proven by sonographically guided 14‐gauge core needle biopsy and their upgrade or malignancy rate after sonographically guided vacuum‐assisted excision or surgical excision. Methods We reviewed the medical records of patients who underwent core needle biopsy from July 2005 to December 2011. We evaluated 39 benign papillomas without atypia in 34 patients. The papillomas were diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…The published literature reports upgrade rates to carcinoma following a diagnosis of benign papilloma at CNB ranging from 0% to 29% [1][2][3]. Some authors believe that benign papillomas diagnosed at CNB with imaging concordance may be safely managed with clinical and imaging follow-up [6,7,[12][13][14][15][16][17][18][19][20]. Others advocate surgical excision to exclude any associated malignancy [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 91%
“…The published literature reports upgrade rates to carcinoma following a diagnosis of benign papilloma at CNB ranging from 0% to 29% [1][2][3]. Some authors believe that benign papillomas diagnosed at CNB with imaging concordance may be safely managed with clinical and imaging follow-up [6,7,[12][13][14][15][16][17][18][19][20]. Others advocate surgical excision to exclude any associated malignancy [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 91%
“…Although the management of benign papillary lesions diagnosed at CNBs is still controversial [26], the current management of benign papillary lesions diagnosed at CNBs is US-guided VAE [47]. Thus, predicting atypical or malignant papillary lesions on US could be helpful for the management.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [2, 3] have reported that surgical excision is recommended for an accurate diagnosis of benign papilloma diagnosed using ultrasound (US)-guided CNB. In contrast, some studies have reported that US-guided vacuum-assisted excision (VAE) is accurate and could be an alternative to surgery for benign papillary lesions [47]. Sohn et al [4] reported no malignancies after excising benign papilloma diagnosed by US-guided CNB.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations